Sistem Latihan Ujian Nasional Mata Pelajaran Bahasa Indonesia dan Bahasa Inggris Berbasis Web Untuk Siswa SMP (Studi Kasus SMP Muhammadiyah 1 Kartasura) - Hurrohmah, Mafati, Heru Supriyono, ST. MSc. PhD (2016)
National exam exercise system is a web-based system used by students to practice or study independently test system using the website so that students use it anytime and anywhere as long as it is connected to the internet. Gradually UNBK (National Computer Based Exam) has started in 2015, the implementation of which is considered successful UNBK will be continued for the following years. Students SMP Muhammadiyah 1 Kartasura not accustomed to using a web-based information system, this study aims to create a training system of the National Examination Based Website for junior high school students in order to train students in the face of National Examination-based computer. The system is built using PHP and MySQL. In this system the student can take a test directly (online) and can clinch exam results. In this study, data collection was done by interview and literature study. Results in the form of National Exam Exercise System Subjects Indonesian and English web-based. Testing is done by means of internal testing and external testing. Internal testing conducted using the Black Box testing while the external testing is done through direct practice and filling questionnaires conducted in SMP Muhammadiyah 1 Kartasura. Based on the result of questionnaires showed that 96.6% of the 20 respondents said that the system is made very useful.